Recent advances and applications of nitroreductase activable agents for tumor theranostic - Shang, Baoxin; Yu, Zongjiang; Wang, Zhengdan (Frontiers in Pharmacology, 2024)
Nitroreductase activable agents offer a personalized and targeted approach to cancer theranostics by selectively activating prodrugs within the tumor microenvironment. These agents enable non-invasive tumor imaging, image-guided drug delivery, and real-time treatment monitoring. By leveraging the enzymatic action of tumor-specific nitroreductase enzymes, cytotoxic drugs are delivered directly to cancer cells while minimizing systemic toxicity. This review highlights the key features, mechanisms of action, diagnostic applications, therapeutic potentials, and future directions of nitroreductase activable agents for tumor theranostics. Integration with imaging modalities, advanced drug delivery systems, immunotherapy combinations, and theranostic biomarkers shows promise for optimizing treatment outcomes and improving patient survival in oncology. Continued research and innovation in this field are crucial for advancing novel theranostic strategies and enhancing patient care. Nitroreductase activable agents represent a promising avenue for personalized cancer therapy and have the potential to transform cancer diagnosis and treatment approaches.